Working with time in contemporary families - Hachet, Benoît (Enfances, Familles, Générations, 2018)
Research Framework: The renewed interest of sociologists for the temporal aspects of social activity offers enlightening perspectives on the functioning of family groups. Social time imposes a framework for the coordination of activities by differing family members, and, like a timespan, it offers the possibility of multiple narrations in the ‘future’. For families, time is both a constraint as well as a resource. Aims: The introduction of this issue of “Family Times” uses the plural to highlight the irreducibility of time to a single dimension, which also begs two questions. How Does Time Build Families? How Do Families Build Time? Methodology: The discussions raised in the introduction to this work show that the sociology of time can shed light on family practices, using both a synchronic and diachronic approach, for the entire group as well as for its constituting members. Results: The temporality of education, like professional activities, constitute a socio-temporal framework which is imposed on families as well as the necessity of building an adapted organizational calendar to best prepare for the future. Adoption levels vary according to social and physical constraints of time depending on gender and social environments. Women play a key role in the organization of family time and the transmission of temporal know how. Conclusions: Time is not an external environment wherein individual and familial activities occur. Family members work time differently, whether separately or together, they fulfil the objectives of reproduction and physical and social aims in a manner which is either strategic and well-planned or opportunistic and scattered. Family time is not only experienced, it is also acted upon. Contribution: In addition to making a contribution to the temporal analysis of family dynamics, this introduction opens rarely explored pathways into how families work the different times that shape them